Primary umbilical endometriosis - SANTOS FILHO,PAULO VICENTE DOS (2018)
ABSTRACT Objective: to report the characteristics, evolution and outcome of patients with primary umbilical endometriosis. Methods: an observational and descriptive study of patients with primary umbilical endometriosis diagnosed between 2014 and 2017. The clinical variables evaluated were age, clinical picture, lesion characteristics, diagnostic methods, treatment and recurrence. Results: six patients diagnosed with primary umbilical endometriosis aged 28 to 45 years were operated on during the study period. They had lesions ranging from one to 2.5cm in diameter, violet in five patients and erythematous-violaceous in one. The duration of the symptoms until diagnosis ranged from one to three years and in all the cases studied the diagnosis was made through the clinical manifestations and confirmed by histopathological analysis. No case was associated with neoplastic alterations. All patients evaluated had pain and umbilical bleeding in the menstrual period. Conclusion: umbilical endometriosis is an uncommon disease and should be included in the differential diagnosis of women as umbilical nodules. The treatment of choice is the total exeresis of the lesion.